Protocol for the TIDAL Melanoma Study: topical imiquimod or diphenylcyclopropenone for the management of cutaneous in-transit melanoma metastases—a phase II, single centre, randomised, pilot study - Read, Tavis (BMJ Open, 2017)
INTRODUCTION: Patients with in-transit melanoma metastases present a therapeutic challenge. Complete surgical excision of localised disease is considered as the gold standard; however, surgery is not always acceptable and alternatives are required. Treatment results reported using imiquimod and diphenylcyclopropenone (DPCP) suggest that topical immunotherapies can be used to successfully treat select patients with melanoma metastases. A phase II, randomised, single centre, pilot study was designed to assess the clinical efficacy and safety of DPCP and imiquimod for the treatment of superficial, cutaneous in-transit melanoma metastases. METHODS AND ANALYSIS: This is an open-label, non-superiority, pilot study with no treatment cross-over. Eligible patients are randomised in a 1:1 ratio to receive topical therapy for up to 12 months with a minimum follow-up period of 12 months. The target sample size is 30 patients, with 15 allocated to each treatment arm. The primary endpoint is the number of patients experiencing a complete response of treated lesions as determined clinically using Response Evaluation Criteria in Solid Tumours. This trial incorporates health-related quality of life measures and biological tissue collection for further experimental substudies. The study will also facilitate a health economic analysis. ETHICS AND DISSEMINATION: Approval was obtained from the Human Research Ethics Committee at the participating centre, and recruitment has commenced. The results of this study will be submitted for formal publication within a peer-reviewed journal. TRIAL REGISTRATION NUMBER: Prospectively registered on 16 October 2015 with the Australian New Zealand Clinical Trials Registry (ACTRN12615001088538). This study conforms to WHO Trial Registration Data Set.